2008
DOI: 10.1038/sj.bjc.6604145
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of soy exposures and breast cancer risk

Abstract: Most of the early studies published on soy and breast cancer were not designed to test the effect of soy; the assessment of soy intake was usually crude and few potential confounders were considered in the analysis. In this review, we focused on studies with relatively complete assessment of dietary soy exposure in the targeted populations and appropriate consideration for potential confounders in the statistical analysis of study data. Meta-analysis of the 8 (1 cohort, 7 case -control) studies conducted in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
301
4
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(343 citation statements)
references
References 39 publications
22
301
4
6
Order By: Relevance
“…The effect of soy on breast cancer risk did not differ by ER/PR status, but the estimated isoflavone intake showed an inverse association with breast cancer risk only among postmenopausal women with ER þ /PR þ tumors. To date, the findings on the effect of soy on breast cancer risk in epidemiological studies have been inconclusive (Trock et al, 2006;Wu et al, 2008b). Large differences in study results exist between the Asian and Western populations; Wu et al (2008b) found a significant trend of decreasing risk with increasing soy consumption from a meta-analysis of the eight studies conducted in Asians, who are large consumers of soy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of soy on breast cancer risk did not differ by ER/PR status, but the estimated isoflavone intake showed an inverse association with breast cancer risk only among postmenopausal women with ER þ /PR þ tumors. To date, the findings on the effect of soy on breast cancer risk in epidemiological studies have been inconclusive (Trock et al, 2006;Wu et al, 2008b). Large differences in study results exist between the Asian and Western populations; Wu et al (2008b) found a significant trend of decreasing risk with increasing soy consumption from a meta-analysis of the eight studies conducted in Asians, who are large consumers of soy.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological and epidemiological studies have suggested that high soy consumption might explain the low incidence of breast cancer in Asian countries compared with Western countries (Pisani et al, 2002;Wu et al, 2008b). Soybeans are the predominant source of isoflavones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies suggest that there indeed is a modest inverse association between high soy food consumption and reduced risk (Trock et al, 2006;Wu et al, 2008). However, several questions remain regarding a causative role of soy consumption in reducing breast cancer risk; the possibility that the association simply reflects other factors/ 'healthy' lifestyle affecting breast cancer risk cannot be excluded at the present time.…”
Section: Genistein and Breast Cancermentioning
confidence: 94%
“…One possible explanation for the discrepancy between the protective role of soy found in two meta-analyses (Trock et al, 2006;Wu et al, 2008) and the lack of effect on biomarkers of breast cancer risk or the results generated in animal studies during adult exposure to soy/genistein is that, to be protective, this bioactive food component may need to be consumed during early life. In support of this argument, epidemiological studies indicate that childhood/adolescence exposure to soy provides protection against breast cancer later in life (Shu et al, 2001;Wu et al, 2002).…”
Section: Genistein and Breast Cancermentioning
confidence: 94%